Genetic Regulation of the Thymic Stromal Lymphopoietin (TSLP)/TSLP Receptor (TSLPR) Gene Expression and Influence of Epistatic Interactions Between IL-33 and the TSLP/TSLPR Axis on Risk of Coronary Artery Disease - Nie, Shao-Fang; Zha, Ling-Feng; Fan, Qian; Liao, Yu-Hua; Zhang, Hong-Song; Chen, Qian-Wen; Wang, Fan; Tang, Ting-Ting; Xia, Ni; Xu, Cheng-Qi; Zhang, Jiao-Yue; Lu, Yu-Zhi; et al. (Frontiers in Immunology, 2018)
The thymic stromal lymphopoietin (TSLP)/TSLP receptor (TSLPR) axis is involved in multiple inflammatory immune diseases, including coronary artery disease (CAD). To explore the causal relationship between this axis and CAD, we performed a three-stage case-control association analysis with 3,628 CAD cases and 3,776 controls using common variants in the genes TSLP, interleukin 7 receptor (IL7R), and TSLPR. Three common variants in the TSLP/TSLPR axis were significantly associated with CAD in a Chinese Han population [rs3806933T in TSLP, Padj = 4.35 × 10−5, odds ratio (OR) = 1.18; rs6897932T in IL7R, Padj = 1.13 × 10−7, OR = 1.31; g.19646A>GA in TSLPR, Padj = 2.04 × 10−6, OR = 1.20]. Reporter gene analysis demonstrated that rs3806933 and rs6897932 could influence TSLP and IL7R expression, respectively. Furthermore, the “T” allele of rs3806933 might increase plasma TSLP levels (R2 = 0.175, P < 0.01). In a stepwise procedure, the risk for CAD increased by nearly fivefold compared with the maximum effect of any single variant (Padj = 6.99 × 10−4, OR = 4.85). In addition, the epistatic interaction between TSLP and IL33 produced a nearly threefold increase in the risk of CAD in the combined model of rs3806933TT-rs7025417TT (Padj = 3.67 × 10−4, OR = 2.98). Our study illustrates that the TSLP/TSLPR axis might be involved in the pathogenesis of CAD through upregulation of mRNA or protein expression of the referenced genes and might have additive effects on the CAD risk when combined with IL-33 signaling.